Interdependent transformations: Integrating insights from relationship science to advance post-traumatic growth and personality change research. Issue 4 (July 2022) - Lamarche, Veronica M
People have a tremendous ability to grow and change for the better following adverse life events. This capacity for growth has captured the attention of psychologists interested in understanding the mechanisms underpinning both personality and well-being. This paper advocates for a greater integration of relationship science into this area of study as a means of advancing post-traumatic growth and personality change research. Relationships, both as an impetus for change and as evidence of growth, have featured consistently in the post-traumatic growth and adversity literatures. Drawing from interdependence theory in particular, this paper highlights how the unique structure of close relationships and relationship dynamics can be applied to address outstanding theoretical questions related to the advancement of post-traumatic growth research as well as offers a critique of the practice of using relationship outcomes (e.g., connection) as evidence of post-traumatic growth. Finally, this paper encourages psychologists across subdisciplines to share their unique skills and insights to help generate more robust psychological theories and methods.